Disrupting Africa : technology, law, and development - Arewa, Olufunmilayo B., 1964- (Cambridge : Cambridge University Press, 2021)
In the digital era, many African countries sit at the crossroads of a potential future that will be shaped by digital-era technologies with existing laws and institutions constructed under conditions of colonial and post-colonial authoritarian rule. In Disrupting Africa, Olufunmilayo B. Arewa examines this intersection and shows how it encompasses existing and new zones of contestation based on ethnicity, religion, region, age, and other sources of division. Arewa highlights specific collisions between the old and the new, including in the 2020 #EndSARS protests in Nigeria, which involved young people engaging with varied digital era technologies who provoked a violent response from rulers threatened by the prospect of political change. In this groundbreaking work, Arewa demonstrates how lawmaking and legal processes during and after colonialism continue to frame contexts in which digital technologies are created, implemented, regulated, and used in Africa today.
Introduction : colonialism and Africa's future paths -- Colonialism, governance and law -- Relationships and accountability -- Legal imperialism and institutions -- Language, authority and law -- Technology disruption and digital colonialism -- Nigerian princes, start-up companies and potential future paths -- Technology, precarity and protest -- Elites, ornamentation and future visions -- Colonial portfolios, monopolies and competition -- Conclusion : ghosts, dreams and future paths.
Title from publisher's bibliographic system (viewed on 20 Jul 2021).
Keywords: Technological innovations -- Law and legislation -- Africa, Sub-Saharan.; Postcolonialism -- Africa, Sub-Saharan.; Disruptive technologies -- Social aspects -- Africa, Sub-Saharan.; Law -- Social aspects -- Africa, Sub-Saharan.; Law and economic development -- Law and legislation -- Africa, Sub-Saharan.